Принципи формування конкурентоспроможного бренду в туристичній галузі - Юрченко, Наталія Іванівна; Yurchenko, Nataliy (Національний авіаційний університет, 2019)
У статті висвітлено принципи формування конкурентоспроможного бренду туристичної галузі України. Проаналізовано основні етапи еволюції понять торгової марки та бренду. Стратегічною метою розвитку індустрії туризму в Україні є створення конкурентоспроможного на внутрішньому та світовому ринках національного туристичного продукту, розширення внутрішнього та збільшення обсягів в‘їзного туризму, забезпечення на цій основі комплексного розвитку курортних територій та туристичних центрів з урахуванням соціально-економічних інтересів населення, збереження та відновлення природних територій всієї країни та історико-культурної спадщини. Брендинг необхідний для індивідуалізації образу підприємства, створення у свідомості споживачів відповідного образу та прихильності до конкретного підприємства; допомагає формувати та підтримувати імідж підприємства, конкурувати на ринку. Також виділені певні моделі розробки стратегічного плану позиціювання нового бренду на туристичному ринку, де проводиться аналіз характеристик бренду, способів його просування, визначається його місце на ринку з обов’язковим урахуванням потреб споживачів та сприйняття бренду споживачами. The article describes the principles of forming a competitive brand of tourism industry in Ukraine. The main stages of the evolution of trademark and brand concepts are analyzed. The strategic goal of the tourism industry development in Ukraine is the creation of a national tourist product, competitive on the domestic and world markets, expanding the internal and increasing volumes of inbound tourism, providing on this basis integrated development of resort areas and tourist centers taking into account socio-economic interests of the population, preservation and restoration of natural territories of the whole country and historical and cultural heritage. The state of development of the tourist services market is accompanied by intensification of entrepreneurial activity, increased competition in the domestic and foreign markets, changes in the needs and preferences of tourists. The survival and development of tourism industry enterprises requires a responsible approach to brand development. Branding is necessary for the individualization of the image of the enterprise, creation of the appropriate image and attachment to the concrete enterprise in the consciousness of consumers; Helps to shape and maintain the image of an enterprise, compete on the market. Also, certain models are developed for the development of a strategic plan for positioning a new brand in the tourism market, where the analysis of brand characteristics, ways of its promotion, its place in the market is determined with the obligatory consideration of consumers' needs and the perception of the brand by consumers. The brand's place in the presentation of consumers in relation to other competitors and is considered a brand position. This determines further tasks, such as analysis of the target audience for which the brand is created; Determine the benefits consumers will receive from this brand; an understanding of the purpose for which the brand is required to achieve. Development of an effective brand management system, that is, brand management, which enables the company to form competitive advantages and function in the market.
Principles for competitive brand formation in the tourism industry
Keywords: бренд; brand; брендинг; branding; туристичний продукт; tourist product; «бренд міста»; “brand of the city”; «бренд країни» та «туристичний бренд»; “brand of the country” and “tourist brand”